1992
DOI: 10.1063/1.107735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal annealing on porous silicon photoluminescence dynamics

Abstract: Photoluminescence (PL) spectra and decay dynamics were studied for the spontaneously oxidized porous Si with subsequent various thermal annealing procedures. The PL decay was highly nonexponential and well described by the stretched-exponential function. The PL lifetime was shorter for the higher PL photon energy, but at the same photon energy it decreased by an order of magnitude by the thermal annealing in N2 gas, in parallel with the large PL intensity decrease. This PL quenching upon the annealing is presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…[43] Annealing treatments induce a quenching of the room temperature luminescence with a decrease in the values of τ and β. [14] Within our model, this is simulated by diminishing…”
Section: Discussionmentioning
confidence: 99%
“…[43] Annealing treatments induce a quenching of the room temperature luminescence with a decrease in the values of τ and β. [14] Within our model, this is simulated by diminishing…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, time-resolved photoluminescence spectroscopy (TRPL) of PS has been extensively studied [2][3][4][5] and some workers have reported that at room temperature the PL decay time ( ) depended strongly on wavelength detection ( ) [6][7][8][9]: decreases with decreasing . For example is 45 s at 700 nm and 5 s at 550 nm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Within "slow" decays, lower energy portion of photoluminescence corresponds to slower decay (small β) and it has narrower distribution of lifetime, i.e. larger γ [16].…”
Section: Phooluminescence and Related Characterizationmentioning
confidence: 99%